Faktor-faktor yang Berhubungan dengan Siklus Menstruasi pada Remaja Putri - Lukman, Widya Utami; Hiola , Fidyawati Aprianti; Sondakh , Levana; Inaku , Hartati (STIKes Hamzar, 2025)
The menstrual cycle is an important indicator of adolescent girls' reproductive health, which can be influenced by various physiological and psychological factors. Menstrual cycle disorders include menorrhagia, oligomenorrhea, polymenorrhea, and amenorrhea, which are generally associated with ovarian dysfunction, anovulation, and luteal phase disorders. If left untreated, these disorders can have long-term impacts on adolescent fertility and quality of life. Management efforts include weight management, regular exercise, adequate rest, stress management, and a nutritious diet. This study aims to determine the factors associated with the menstrual cycle in adolescent girls at MAN 1, Gorontalo City. The study used a quantitative approach with a cross-sectional design. A sample of 75 respondents was drawn using accidental sampling. The research instruments consisted of questionnaires and BMI measurements, with data analysis using the Chi-Square test. The results showed a significant relationship between BMI (p = 0.001) and a history of disease (p = 0.004) and the menstrual cycle, and no significant relationship between stress levels and the menstrual cycle (p = 0.599). It was concluded that BMI and a history of disease were related to menstrual cycle regularity, while stress was not related to the menstrual cycle. This study is expected to serve as a reference for adolescent reproductive health education and interventions.